Spatial Distribution of Attention during Attentional Blink is Influenced by Eye Movements. (September 2013) - Du, Feng; Qi, Yue; Zhang, Kan
The present study examined three factors that might influence the spatial distribution of attention after the identification of a first target during attentional blink: The maximum distance between the two targets, the spatial configuration of stimuli, and eye movements. Results showed that the U-shaped distribution of attention during attentional blink persisted in the circular configuration of stimuli irrespective of the radius of the circle. In addition, the U-shaped distribution of attention during attentional blink depends on the circular configuration of stimuli and the central fixation. When two targets appeared in noncircular configurations and eye movements were not strictly restrained, a large proportion of observers showed a gradient for the accuracy of the second target (T2) during attentional blink. However, when observers kept fixating on the central cross in a noncircular configuration, they showed a U-shaped distribution of T2 performance during attentional blink. Furthermore, observers are more likely to show a gradient distribution of T2 performance during attentional blink as their probability of fixating the first target (T1) increases. These results suggest that maintaining equal eccentricity for each stimulus is critical for producing the U-shaped distribution of attention during attentional blink.